Principal's Management Competency In Following Up Curriculum Development at SDN 11 Air Kumbang - Silvia Tri Utami; Syarwani Ahmad; Wahid Ibrahim Banul Ngindom (International Journal of Social Sciences and Humanities, 2026)
The study at SDN 11 Air Kumbang aimed to analyze the principal's managerial competency in following up on curriculum development, assess the effectiveness of clinical supervision and ongoing professional development, and identify barriers and supports for transformational leadership. Using descriptive qualitative methods through interviews, observation, and documentation, the informants in this study included the principal, student representatives, teachers, and school operators. The results showed that the principal possessed adequate skills in designing curriculum follow-up through regulatory review and participatory planning with all stakeholders. Managerial functions were effective through routine clinical supervision, providing constructive feedback, and facilitating teacher development through In-House Training (IHT) and the use of the Merdeka Mengajar (PMM) Platform. The principal's transformational leadership was a key factor in building an adaptive vision and culture, despite still facing limited infrastructure and technical challenges in digital data management due to inadequate internet connectivity at the school. Overall, managerial competency and transformational leadership played a crucial role in the successful implementation of the curriculum through optimizing existing resources and strengthening internal collaboration within the school.